Study on the Case Laws Registered Regarding Cyber Crime against Women: Understanding the Impact and Legal Aspects of Cyber Crimes against Women (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The offices of computer technology have not turned out without downsides. In spite of the fact that it makes the life so quick and quick, however heaved under the shroud of threat from the deadliest sort of guiltiness named as 'Cyber crime' without computers, whole organizations and government tasks would nearly stop to work. The expanding reach of the internet, the quick spread of portable information, and the across the board utilization of social media, combined with the current pandemic of violence against women and girls (VAWG), has prompted the rise of cyber VAWG as a developing global issue with possibly huge monetary and societal results. The directly to internet utilization has now turned into a human ideal, as announced by the United Nations Human Rights Council in June 2016. Cyber-crimes use information technology and the internet as the essential methods for commission of illegal activities, which are restricted and deserving of criminal law of the land. While cyber-crimes might be carried out against persons, property and the government, this paper centers around cyber-crimes against women. In this research paper we studied about the Concept of Cyber crimes against Women, their categories, reasons leading to their Growth and the Case laws concerning it.